Conservative management of Caesarean scar pregnancies with systemic multidose methotrexate: predictors of treatment failure and reproductive outcomes. Issue 5 (November 2019) - Levin, Gabriel; Zigron, Roy; Dior, Uri P; Gilad, Ronit; Shushan, Asher; Benshushan, Avi; Rottenstreich, Amihai
Abstract: Research question: Caesarean scar pregnancy (CSP) is an increasing concern in modern obstetrics. Early diagnosis and management are of utmost importance. The optimal management approach for CSP is not well established, with various treatment modalities reported. The role of conservative management of CSP has been previously reported, with conflicting results. This study aimed to further evaluate its role and better delineate the subsequent reproductive outcomes. Design: A retrospective cohort study including all patients diagnosed with a CSP and treated by intention of conservative management with systemic methotrexate (MTX). Maternal and gestation characteristics were compared between treatment success and failure groups. Results: Thirty-six cases of CSP were encountered. Overall, 29/36 (80.6%) were treated by systemic injection of MTX while the other 19.4% had combined systemic and local (i.e. intra-sac) MTX treatment. Invasive intervention was needed in five (13.9%) cases (failure group). Among those successfully treated with MTX, the median time to resolution was 22 (interquartile range 13–37) days. Cases who were converted to surgical treatment had a higher number of previous Caesarean deliveries (median 4 versus 2, P  = 0.002). In logistic regression modelling, the number of previous Caesarean deliveries was the only factor independently associated with conversion to surgical management (odds ratio 2.02, 95% confidence interval 1.03–3.94). The majority of future pregnancies ended at term pregnancy with only one preterm delivery due to severe intrauterine growth restriction. Conclusions: Systemic MTX therapy is a safe and effective strategy for the treatment of CSP, with favourable subsequent reproductive results and a low conversion rate to surgical management.